1979
DOI: 10.1051/rphysap:01979001408074300
|View full text |Cite
|
Sign up to set email alerts
|

Linearization of polycrystalline film gauge factors

Abstract: A linearized equation is proposed to describe the thickness dependence of the polycrystalline film gauge factor γF. Finally the theoretical variation of γF is represented by a general equation whose form is similar to those related to linearized equations previously derived for analyzing polycrystalline film resistivity and T.C.R. Comparisons of exact and approximate values indicate a deviation less than 10 % over large ranges of the surface scattering specularity parameter, p, the average random distance betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1982
1982

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Further extensions are probable since the thermoelectric power can be expressed in term of t.c.r. [24, 251, when the effects of thermal strains [26, 271 are neglected; it has also been recently demonstrated that it is also the case for the Hall coefficient [17] and probably for strain coefficients of resistivity [28].…”
Section: Introductionmentioning
confidence: 99%
“…Further extensions are probable since the thermoelectric power can be expressed in term of t.c.r. [24, 251, when the effects of thermal strains [26, 271 are neglected; it has also been recently demonstrated that it is also the case for the Hall coefficient [17] and probably for strain coefficients of resistivity [28].…”
Section: Introductionmentioning
confidence: 99%